Durable Nanofluids‐Infused Hierarchical Surfaces with High Corrosion and Abrasion Resistance. Issue 8 (12th January 2023) - Wang, Shuqiang; Wang, Shuxia; Xue, Yanpeng; Xue, Yanyan; Liu, Quanyou; Cao, Lili; Nie, Mengyan; Jin, Ying
Abstract : The design of robust and durable ultra‐lubricated surfaces having an efficient corrosion resistance ability is concerned with practical applications. Here a new optimized strategy to significantly improve the performance of ultra‐lubricated surfaces by injecting slippery nanofluids into the hierarchical surfaces (SNHSs) is proposed. Herein, cobalt–nickel hierarchical surfaces reinforced by micro SiO2 particles are achieved on carbon steel substrate by electrochemical deposition and the functionalized nanofluids are injected into the hierarchical structure. Compared with nanostructured ultra‐lubricated surfaces, SNHSs exhibit better lubricity and corrosion resistance when subjected to water flow shear for more than 20 h. The tribo‐electrochemical tests are introduced to demonstrate that the SNHS has a lower coefficient of friction (0.39), more shallow wear marks (5 μm), and more complete surface morphology by directly comparing the wear resistance and self‐healing ability. The hierarchical substrate has more advantages than the nanostructured substrate in the practical application of ultra‐lubricated surface. Furthermore, the SNHS with robust mechanical durability can be a promising alternative technique for corrosion protection. Abstract : A new optimized strategy to improve the performance of ultra‐lubricated surfaces by injecting slippery nanofluids into the hierarchical surfaces (SNHSs) is proposed. Compared with nanostructured ultra‐lubricated surfaces, SNHS exhibits better lubricity and corrosion resistance when subjected to water flow shear for more than 20 h. The hierarchical substrate has more advantages than the nanostructured substrate in practical application.